Relationship between pharmacology and Florence Nightingale’s theory - López Gamboa, Yoel; Gamboa Pellicier, Yoeldis; Rodríguez Cantillo, Yanet (Seven Editora, 2023)
In the mid-nineteenth century, nursing as a profession was founded by Florence Nightingale, although it was not until the second half of the twentieth century that significant advances were truly made in the development of the profession. With the aim of establishing the relationship that exists between Florence Nightingale’s theory and Pharmacology, the present work was carried out. A bibliographic review of the current state of the subject was made in the Google academic, SciELO, Dialnet, and PubMed databases, with the keywords: Chronobiology, Chronopharmacology, Biological rhythms and Chronopharmokinetics. In this review, it was evidenced that there is a direct association between the time of day in which the drugs are administered, and the pharmacological effects, especially due to changes in their pharmacokinetic variability, factors that also influence their safety, and in pharmacodynamics. The physiological processes that occur in our body follow the course of biological rhythms, so they must be taken into consideration in pharmacotherapy in order to guarantee greater therapeutic efficacy and greater safety. The elements described allow us to affirm the relationship between nature and man, as postulated by Nightingale, and pharmacology. DOI: 10.56238/pacfdnsv1-012